Green Facades in Addressing Climate Change: Thermal Performance in a Multifamily Building in Hot and Humid Climate - Borges, Camila Mauro; Pagel , Érica Coelho (Technical and Scientific Journal Green Cities, 2025)
Objective – To demonstrate the impact of implementing green facades on the thermal and energy performance of a multifamily building in Vitória/ES, considering future climate scenarios.Methodology – The study used computational simulation to compare the performance of a baseline case (existing building) with an intervention case (with green facade), analyzing data on thermal comfort, energy consumption, and peak temperatures for the current scenario, 2050, and 2090.Originality/Relevance – The research addresses the need for urban adaptation strategies to climate change in hot and humid climates, providing a quantitative analysis of the benefits of a nature-based solution, with academic and social relevance.Results – The green facade significantly increased the days and hours of thermal comfort, reduced energy consumption for air conditioning by up to 703 kWh/year and mitigated peak temperatures by up to 3.3°C, demonstrating its effectiveness as an adaptation measure.Theoretical/Methodological Contributions – The study provides a comparative analysis method for the performance of green facades in different climate scenarios, contributing to future research in the field.Social and Environmental Contributions – It highlights the potential of green facades to improve urban quality of life, reduce the carbon footprint of buildings, and promote city resilience in the face of climate challenges, generating direct benefits for society and the environment.
Keywords: Green Facades; Climate Change; Thermal Comfort; Energy Efficiency; Urban Adaptation